PENERAPAN METODE REWARD DAN PUNISMENT DALAM PEMBINAAN DISIPLIN DAN PRESTASI MAHASANTRI MA’HAD AL-JAMI’AH IAIN CURUP - Tri Wati (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2020)
This research  is motivated by the implementation of reward and punisment methods that are applied  at the Ma’had Al-Jami’ah IAIN Curup  as an effort to improve  discipline and achievement, this method is suitable for use because it can have a happy  and  deterrent effect but most of students  still have  lower discipline and  achievement. This research  aims to explain the implementation, factors and  benefits  of reward  and  punisment method in improving  discipline and  achievement mahas- antri. This study uses field research  methods with qualitative  descriptive  analysis, data  sources  used  are primary  data  sources and  secondary data  sources,  data  collection using observation, interview and  documentation techniques and  using analytical techniques namely  data  collection,  data  reduction, data  presentation and  the conclusions,  as for the validity of the data  the researcher used  source  triangulation. The results showed  that the implementation of the reward  method and  punisment were applied  in accordance with the existing regulations  but the rewards  were very limited and  only given once  a year in a gebyar ma’had  activity, while the punisment was given by the ma’had  management so that there  were still many  students  breaking, the factor of the implementation of this reward method is mahasantri and the benefits of implementation of this reward method can add  to the spirit of learning,  learning  to be responsible, and  familiarize  the mahasantri practice  discipline appreciate the time and obey the rules